Lateral black phosphorene P–N junctions formed via chemical doping for high performance near-infrared photodetector - Zhang, Shengli (2016)
Black phosphorene (BP), a newly discovered elemental two-dimensional material, is attractive for optoelectronic and photonic applications because of its unique in-plane anisotropy, thickness-dependent direct bandgap and high carrier mobility. Since its discovery, black phosphorene has become an appealing candidate well-suited for polarization-resolved near- and mid-infrared optoelectronics due to its relative narrow bandgap and asymmetric structure. Here, we employ benzyl viologen (BV) as an effective electron dopant to part of the area of a (p-type) few-layer BP flake and achieve an ambient stable, in-plane P–N junction. Chemical doping with BV molecules modulates the electron density and allows acquiring a large built-in potential in this in-plane BP P–N junction, which is crucial for achieving high responsivity photodetectors and high quantum efficiency solar cells. As a demonstrative example, by illuminating it with a near-infrared laser at 1.47 µm, we observe a high responsivity up to ~180 mA/W with a rise time of 15 ms, and an external quantum efficiency of 0.75%. Our strategy for creating environmentally stable BP P–N junction paves the way to implementing high performance BP phototransistors and solar cells, which is also applicable to other 2D materials.